Isothermal inactivation of Mycobacterium avium subsp. paratuberculosis in curd simulating the stretching phase in pasta-filata cheese process - Barsi, Filippo; Dalzini, Elena; Russo, Simone; Cosciani-Cunico, Elena; Monastero, Paola; Arrigoni, Norma; Garbarino, Chiara Anna; Cortimiglia, Claudia; Losio, Marina Nadia; Ricchi, Matteo (Frontiers in Microbiology, 2022)
Raw milk and dairy products are usually considered the major sources of Mycobacterium avium subsp. paratuberculosis (MAP) exposure for humans. During the production process of mozzarella cheese, a typical Italian pasteurized or raw milk cheese, curd is heated and stretched by addition of hot water (from 60 °C to 99 °C). This step is the critical point for the inactivation of MAP during the production process, but, to our knowledge, no studies have been published about the thermal death time values of MAP in curd. The aim of this study was to determine the inactivation kinetics of MAP in curd used to produce mozzarella cheese in six independent experiments. The milk was inoculated with a mix of MAP strains (field and registered strains) and the curd was manufactured according to mozzarella production specifications. With the aim to simulate the thermal treatment of the curd during the stretching step, samples of 10 g of contaminated curd were vacuum packed and treated separately at six different temperatures from 60 °C to 75 °C in a water bath. MAP survival was then evaluated by plate count method and inactivation parameters were estimated for determining the thermal resistance of the pathogen directly in the curd. D-values increased from 0.15 min (D75-value) to 4.22 min (D60-value) and the calculated z-value was 10.2 °C. These data aid: i) to design food thermal process treatments defining acceptance limits of critical control points to ensure safety against MAP; ii) to predict the time/temperature combinations needed to obtain a certain MAP log reduction during the curd stretching step; iii) to optimize or validate pasta-filata cheese process.